Rare case of Visceral form of Infectious Mononucleosis in Irkutsk Region - N. K. Bobrova; E. Yu. Zorkaltseva (Acta Biomedica Scientifica, 2019)
Infectious mononucleosis (MI) is caused by the Herpes viridae family of viruses. Currently, most researchers assign a leading role to the Epstein-Barr virus. In present time there are no unified clinical classification of infection mononucleosis, but many authors recognize the visceral form which involves cardiovascular system, adrenal glands, lungs, central neural system and others organs. The article describes a clinical case of MI in the 28-year-old patient. She applied for medical help with complaints of fever up to 39 °C, weakness in the legs and arms, weight loss and received symptomatic treatment on an outpatient department. After 2 months on the background of deterioration, she was hospitalized in an infectious diseases hospital with severe symptoms of intoxication, lymphoproliferative syndrome, myocarditis, pericarditis, hepatitis, polyneuropathy with quadriparesis, hypochromic anemia, thrombocytopenia. She was consulted by an oncologist and diagnosed with cervical cancer. Laboratory confirmation was obtained – Epstein-Barr virus was detected in the blood. Against the background of antiviral therapy, a regression of clinical symptoms was achieved in a week. The patient was transferred to a oncological hospital. It is recommended to examine patients with high fever of unknown etiology on myocardial infarction for the timely appointed etiotropic therapy.